2010
DOI: 10.1097/mcp.0b013e32833b1e1f
|View full text |Cite
|
Sign up to set email alerts
|

Metaiodobenzylguanidine scintigraphy in pulmonary and cardiac disease

Abstract: At this moment, there is no added clinical value to routinely use MIBG scanning of the lungs and the heart. This is partly due to the many unresolved questions such as what actually happens and which factors influence MIBG uptake and washout under normal physiological circumstances. But the technique, if standardized and when dynamic time acquisition is performed with the latest equipment, such as PET and single photon emission computed tomography-computed tomography (SPECT-CT), has a tremendous potential. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although extracellular 123 I-MIBG increases because of decreased extraction of circulating 123 I-MIBG to damaged AECs and sympathetic neurons, decreased perfusion disrupts back-diffusion of this component to systemic circulation (15,17,21). Lack of integrity or dysfunction of AECs in PE patients also decreases the 123 I-MIBG washout rate, as various other lung disorders with injury of AECs persistently show a decreased 123 I-MIBG washout rate (16,18,(20)(21)(22)(23)34).…”
Section: Rgbmentioning
confidence: 99%
See 1 more Smart Citation
“…Although extracellular 123 I-MIBG increases because of decreased extraction of circulating 123 I-MIBG to damaged AECs and sympathetic neurons, decreased perfusion disrupts back-diffusion of this component to systemic circulation (15,17,21). Lack of integrity or dysfunction of AECs in PE patients also decreases the 123 I-MIBG washout rate, as various other lung disorders with injury of AECs persistently show a decreased 123 I-MIBG washout rate (16,18,(20)(21)(22)(23)34).…”
Section: Rgbmentioning
confidence: 99%
“…123 I-metaiodobenzylguanidine ( 123 I-MIBG) shares the same uptake as norepinephrine in AECs (12)(13)(14)(15). 123 I-MIBG scintigraphic studies have been used to detect and assess the functional injury or integrity of AECs in various lung diseases, including PE (16)(17)(18)(19)(20)(21)(22)(23). SPECT provides better assessment of lung 123 I-MIBG uptake than planar scanning and allows cross-sectional comparisons with lung morphologic CT scans and perfusion SPECT scans.…”
mentioning
confidence: 99%
“…The lungs extract circulating NE by a specific transporter located in the vascular endothelium and this biologic function has been exploited for molecular imaging of the pulmonary vasculature. This energy-dependent process was imaged using 123 I-metaiodobenzylguanidine (MIBG) scintigraphy, studying the lung uptake and wash-out of the radioimaging agent [ 69 ]. Studies have shown diminished lung extraction of 123 I-MIBG in patients with chronic obstructive pulmonary disease, pulmonary fibrosis, vasculitis, and after radiotherapy and high altitude hypoxia [ 70 – 74 ].…”
Section: Molecular Imaging Of the Pulmonary Vasculaturementioning
confidence: 99%
“…Despite its potential, this agent is not currently used for diagnosis of lung vascular disorders. The lung imaging technique with 123 I-MIBG has never been standardized and the biology of the tracer remains uncertain as lung neuronal uptake, in addition to endothelial uptake, likely contributes to the kinetics of this tracer [ 69 ].…”
Section: Molecular Imaging Of the Pulmonary Vasculaturementioning
confidence: 99%